ChemInform Abstract: Rhodium(I) Complexes Containing 9, 10‐Phenanthrenequinone‐N‐substituted Thiosemicarbazone Ligands: Synthesis, Structure, DFT Study and Catalytic Diastereoselective Nitroaldol Reaction Studies. Issue 49 (December 2015) - Anitha, P.; Manikandan, R.; Vijayan, P.; Anbuselvi, S.; Viswanathamurthi, P.
Abstract: The title Rh(I)‐complexes are found to be efficient catalysts in the asymmetric Henry reaction in ionic liquid [emim]BF4 .